Principal Features of Family Social Capital in Russian Regions: The Case of Vologda Region - Guzhavina, Tatiana (Journal of Sociology: Bulletin of Yerevan University, 2020)
The article is devoted to the study of family social capital. On the basis of a theoretical model, based on the conceptual developments of J. Coleman and P. Bourdieu, an analysis of empirical data obtained in the course of a sociological study conducted in the Vologda Oblast was carried out. It was found that most of the families have the resources to form their social capital and invest in it. However, it is distributed extremely unevenly. A narrow radius of trust does not promote the growth of social capital. Its deficiency can further restrict its transmission to the next generations.